Articulation of environmental management in projects of non-conventional energy sources in the Caribbean Colombian region (2018)
This work addresses an inclusion methodology based on criteria for the implementation of non-conventional energy sources and critical environmental factors for the licensing of the same, which is applied to the case study installation of wind turbines in seawater desalination plants in Isla Grande - Bolívar, this study was carried out taking into account field visits, and previous studies, where its main researchers and observers coincide with the authors of this article, the proposal includes aspects that involve the matrix of project stakeholders, work is completed with the qualitative and quantitative analysis of the factors of greater environmental impact, within the obtained results it is emphasized that the greatest impact that this project makes to 170 habitants of Isla Grande Bolivar is the changes of the current and/or potential use of soil, soil contamination and displacement of birds, In mammal, reptile and amphibian communities, it is suggested that Environmental Management Plans (PMA) be implemented, such as programs for conservation management, soil resource management, and vegetation and wildlife management programs, allowing for effective licensing of the project benefiting equally the interest group.